Cutaneous manifestations of diabetes mellitus: a clinical study - Bhardwaj, Nancy; Roy, Samarjit; Jindal, Rashmi; Ahmad, Sohaib (International Journal of Research in Dermatology, 2018)
Background: Diabetes mellitus is a leading cause of morbidity with adverse effects on various systems including skin. Cutaneous manifestations seen in diabetes aid in its diagnosis and some of them may also correlate with diabetic control, duration and other complications. This study was undertaken to estimate burden of skin disorders among diabetics in a tertiary care centre of Uttarakhand. Methods: The study was conducted at Himalayan Institute of Medical Sciences, Dehradun, Uttarakhand, India, over a period of one year from January 2016 to December 2016. Three hundred and seventy seven patients irrespective of age and sex were included in the study and those with gestational diabetes were excluded. Patients were examined for mucocutaneous manifestations and evaluated. Structured case reporting form was used to generate data. Results: Out of 377 patients studies, 114 (30.2%) were in the age group of 51-60 years. Male to female ratio was 1.44:1. Mucocutaneous manifestations were present in 278/377 (73.7%) patients. Common cutaneous manifestations were cutaneous infections [fungal infections (n=106/377; 28.1%), bacterial infections (n=33/377; 8.8%)], pruritus (n=47/377; 12.5%), xerosis (n=39/377; 10.3%), diabetic dermopathy (n=36/377; 9.5%) and diabetic ulcers (n=24/377; 6.4%). Uncommon manifestations were necrobiosis lipoidica diabeticorum, alopecia areata, scleredema diabeticorum and granuloma annulare. Cutaneous reactions due to treatment of diabetes were noted in 4 (1%) patients. Conclusions: As prevalence of cutaneous manifestations is high in diabetic patients, knowledge of these will help in a timely and comprehensive management of both diabetes and dermatoses.